Consumers’ sustainability-related perception of and willingness-to-pay for food packaging alternatives - Herrmann, Christoph; Rhein, Sebastian; Sträter, Katharina Friederike (Resources, conservation and recycling, 2022)
•Perception of and willingness-to-pay for plastic packaging alternatives analyzed.•Mixed-method study: discrete choice experiment and qualitative free-text analysis.•Positive willingness-to-pay (WTP) for perceived sustainability.•No WTP for perceived lack of sustainability or in case of uncertainty.•Participants are generally dissatisfied with current (plastic) packaging practice. Research regarding consumers’ perception of and willingness-to-pay for alternatives to conventional plastic packaging reveals an ambiguous picture. On one hand, consumers are said to be neither willing to change their consumption behavior nor to pay for alternatives. On the other hand, there is evidence that consumers have an increasing environmental awareness and a positive willingness-to-pay for packaging alternatives. The mixed-method study (Discrete Choice Experiment and qualitative free-text analysis) described in this paper, elucidates the role of consumers and analyzes both consumers’ sustainability-related perception of and willingness-to-pay for alternative food packaging (unpackaged, paper, recycling plastic, bioplastic). Results demonstrate that consumers are willing to pay for packaging that they perceive to be sustainable and are not willing to pay for packaging that they perceive to be non-sustainable or about which they are uncertain. Considering the general disagreement on what kind of packaging actually is sustainable, these results raise the question: if neither theorists, nor companies, nor government agree on the sustainability of different types of packaging – how are consumers supposed to make correct assessments? Besides, results demonstrate that consumers are largely united in their general dissatisfaction with the current packaging situation, even though they are aware of the positive characteristics of single-use plastic packaging.